Effect of Gentamicin on common carp Fish Cyprinus carpio on Diyala province (Histopathological study) - Mahmood, Mohammed Abed (Diyala Journal for Veterinary Sciences, 2023)
Different types of antibiotics are found in water due to water waste excreted by fish, which poses a threat to the public health system, especially human health. Gentamicinis one of the important antibiotics used to treat many bacterial infections in veterinary medicine, so it is widely present in the fishes aquatic environment. The current study aim to identify the effect of gentamicin on the juveniles of common carp (Cyprinus carpio) and reported histopathological changes on gills and liver of it. Fish exposed for 72 h to different concentration of gentamicin. The gills lesions were recorded In control group showed normal histological morphology. Exposed of fish gill to 0.01mg/L and 0.1mg/L of gentamicin showed epithelial cell hyperplasia in addition to hyperplasia of mucous cells, fusion of lamellae , exposed to 1mg/L of gentamicin showed lifting of gill lamella and desquamation and exposed to 10 mg/L, the gill showed aneurysm. Liver histopathology of fish control group not exposed to gentamicin and not showed any histological changes which characterized by presences of normal hepatocytes and hepatocytic nucleus. Exposed to 0.01 not showed any abnormal tissue structure, Fish liver exposed to 0.1mg/L showed only vacuolation, dilation in space between sinusoids and pyknosis, exposed to 1mg/L showed hepatocyte hyper atrophy and degeneration, exposed to 10μg/L showed inflammatory cells infiltration. This study observed the increase doses of gentamicin conjugate with increase severity of lesions in gill and liver especially when not reported any signs in control group for both organ. In addition to that there is circulatory signs such as congestion and dilation of sinusoids in liver. The doses which used in this study consider sub lethal doses, here it must be taken into consideration that doses higher than those used in this current study could cause severe pathological effects in fish.